PERGESERAN NILAI-NILAI RELIGIUS DAN SOSIAL DI KALANGAN REMAJA PARA ERA DIGITALISASI - Murjani Murjani (EDUCATIONAL JOURNAL : General and Specific Research, 2022)
In the religious context, the shift in religious values appears in the youth's enthusiasm to study religious knowledge by attending various recitations carried out. This can be seen by the decreasing number of teenagers who are active in various religious activities and other recitations. Teenagers tend to choose activities such as hanging out, playing a play station (warnet) etc. Hanging out with friends, either in cafes or in parks, has become a sight that can be seen at this time. Another example is that young teenagers today prefer to read comics or play games rather than having to read religious books.